Differences in Academic Saturation Levels of Students at National Senior High Schools in Malang Based on Gender - Nofira Rina Cahyani; Victoria Luong; Soram Goutam (Education Specialist, 2024)
This study aims to determine the differences in academic saturation levels of SMA Nasional Malang students based on gender. This study uses a comparative descriptive design with a quantitative approach. This study used 196 respondents obtained through a cluster random sampling technique. The data collected were inventory and analyzed using the hypothesis test (t). Based on the results of the analysis, it is known that the t statistic value obtained was 1.313 and the p value (P-value) obtained was 0.180. It can be concluded that there is no significant difference between male and female gender on academic saturation of SMA Nasional students. This means that gender does not affect the level of academic saturation of students.